Volatile anesthetics isoflurane and sevoflurane directly target and attenuate Toll‐like receptor 4 system. Issue 12 (2nd November 2019) - Okuno, Toshiaki; Koutsogiannaki, Sophia; Hou, Lifei; Bu, Weiming; Ohto, Umeharu; Eckenhoff, Roderic G.; Yokomizo, Takehiko; Yuki, Koichi
Abstract : General anesthesia has been the requisite component of surgical procedures for over 150 yr. Although immunomodulatory effects of volatile anesthetics have been growingly appreciated, the molecular mechanism has not been understood. In septic mice, the commonly used volatile anesthetic isoflurane attenuated the production of 5‐lipoxygenase products and IL‐10 and reduced CD11b and intercellular adhesion molecule‐1 expression on neutrophils, suggesting the attenuation of TLR4 signaling. We confirmed the attenuation of TLR4 signaling in vitro and their direct binding to TLR4‐myeloid differentiation‐2 (MD‐2) complex by photolabeling experiments. The binding sites of volatile anesthetics isoflurane and sevoflurane were located near critical residues for TLR4‐MD‐2 complex formation and TLR4‐MD‐2‐LPS dimerization. Additionally, TLR4 activation was not attenuated by intravenous anesthetics, except for a high concentration of propofol. Considering the important role of TLR4 system in the perioperative settings, these findings suggest the possibility that anesthetic choice may modulate the outcome in patients or surgical cases in which TLR4 activation is expected.—Okuno, T., Koutsogiannaki, S., Hou, L., Bu, W., Ohto, U., Eckenhoff, R. G., Yokomizo, T., Yuki, K. Volatile anesthetics isoflurane and sevoflurane directly target and attenuate Toll‐like receptor 4 system. FASEB J. 33, 14528‐14541 (2019). www.fasebj.org